Endoscopic management of ampullary tumors: European Society of Gastrointestinal Endoscopy (ESGE) Guideline - Vanbiervliet, Geoffroy; Strijker, Marin; Arvanitakis, Marianna; Aelvoet, Arthur; Arnelo, Urban; Beyna, Torsten; Busch, Olivier; Deprez, Pierre H.; Kunovsky, Lumir; Larghi, Alberto; Manes, Gianpiero; Moss, Alan; Napoleon, Bertrand; Nayar, Manu; Pérez-Cuadrado-Robles, Enrique; Seewald, Stefan; Barthet, Marc; van Hooft, Jeanin E. (Endoscopy, 2021)
1 ESGE recommends against diagnostic/therapeutic papillectomy when adenoma is not proven.Strong recommendation, low quality evidence.2 ESGE recommends endoscopic ultrasound and abdominal magnetic resonance cholangiopancreatography (MRCP) for staging of ampullary tumors.Strong recommendation, low quality evidence.3 ESGE recommends endoscopic papillectomy in patients with ampullary adenoma without intraductal extension, because of good results regarding outcome (technical and clinical success, morbidity, and recurrence).Strong recommendation, moderate quality evidence.4 ESGE recommends en bloc resection of ampullary adenomas up to 20–30 mm in diameter to achieve R0 resection, for optimizing the complete resection rate, providing optimal histopathology, and reduction of the recurrence rate after endoscopic papillectomy.Strong recommendation, low quality evidence.5 ESGE suggests considering surgical treatment of ampullary adenomas when endoscopic resection is not feasible for technical reasons (e. g. diverticulum, size > 4 cm), and in the case of intraductal involvement (of > 20 mm). Surveillance thereafter is still mandatory.Weak recommendation, low quality evidence.6 ESGE recommends direct snare resection without submucosal injection for endoscopic papillectomy.Strong recommendation, moderate quality evidence.7 ESGE recommends prophylactic pancreatic duct stenting to reduce the risk of pancreatitis after endoscopic papillectomy.Strong recommendation, moderate quality evidence.8 ESGE recommends long-term monitoring of patients after endoscopic papillectomy or surgical ampullectomy, based on duodenoscopy with biopsies of the scar and of any abnormal area, within the first 3 months, at 6 and 12 months, and thereafter yearly for at least 5 years.Strong recommendation, low quality evidence.